Implementing an andragogical approach to foreign language training of adult military learners - Sovhar, Oksana (Educological discourse, 2026)
The article addresses the issue of enhancing foreign language communication training for future officers in higher military education institutions under conditions of ongoing war and intensified international cooperation. The purpose of the study is to theoretically substantiate the conceptual foundations of the andragogical approach to foreign language communication training of adult military learners within higher military education and to identify methodological principles associated with its implementation. The research employs a qualitative theoretical methodology, incorporating analytical, comparative, structural-logical, and interpretative methods applied to scientific, pedagogical, and regulatory sources in the field of military education. The study indicates that the andragogical approach, based on the principles of self-directed learning, reliance on professional experience, problem-centeredness, and practical orientation, provides a conceptual basis for organizing more professionally relevant foreign language training for future officers. The results outline that experience-based learning, contextual modelling of professional situations, simulations, role-plays, project-based tasks, and blended learning technologies are methodologically consistent with the andragogical framework and may facilitate the development of communicative competence required for participation in multinational military environments, interoperability, and joint training activities. The findings also emphasize the importance of redefining the instructor’s role as a facilitator who supports reflection, feedback, and individualized learning trajectories. The study concludes that the systematic integration of andragogical principles into foreign language training constitutes a theoretical and methodological framework for improving military language education and highlights the need for its further development in line with contemporary operational and interoperability requirements.